A new species of Passiflora supersect. Decaloba (Passifloraceae) from the central-eastern Andes of Colombia - Kuethe, J.r.; Fredy Rojas, Jhon; Bernal P., Hernan D. (Phytotaxa, 2025)
A new species of genus Passiflora is described following targeted fieldwork to the eastern Andes of Boyacá department in Colombia between June 2021 and December 2023. This new species shows taxonomic relation to the widely distributed P. alnifolia and P. chelidonea, for which it was invariably identified during previous herbarium collections. However, following new living material and detailed studies of specimens found both in situ and grown ex situ by the authorial team it was soon deduced that these maintain consistent differences warranting recognition as new species separate from the Passiflora alnifolia alliance. This paper introduces Passiflora mamapachae sp. nov., a new species of subgenus Decaloba supersect. Decaloba, found within a small regional distribution containing montane transitional forests of Boyacá. Its inherent morphology, ecology and distribution, including comments on its association with the other species from this taxonomic alliance are here discussed.